(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the history of the short story genre and its introduction into Uzbek literature were studied. The specific features of this genre were analyzed based on the short story "Question" by writer Khurshid Dostmuhammad. The system of images in the work, the writer’s artistic concept is studied.